Comparison of Fresh Frozen Tissue With Formalin-Fixed Paraffin-Embedded Tissue for Mutation Analysis Using a Multi-Gene Panel in Patients With Colorectal Cancer - Gao, Xian Hua; Li, Juan; Gong, Hai Feng; Yu, Guan Yu; Liu, Peng; Hao, Li Qiang; Liu, Lian Jie; Bai, Chen Guang; Zhang, Wei (Frontiers in Oncology, 2020)
Background: Next generation sequencing (NGS)-based multi-gene panel tests have been performed to predict the treatment response and prognosis in patients with colorectal cancer (CRC). Whether the multi-gene mutation results of formalin-fixed paraffin-embedded (FFPE) tissues are identical to those of fresh frozen tissues remains unknown. Methods: A 22-gene panel with 103 hotspots was used to detect mutations in paired fresh frozen tissue and FFPE tissue from 118 patients with CRC. Results: In our study, 117 patients (99.2%) had one or more variants, with 226 variants in FFPE tissue and 221 in fresh frozen tissue. Of the 129 variants identified in this study, 96 variants were present in both FFPE and fresh frozen tissues; 27 variants were found in FFPE tissues only; 6 variants were found only in fresh frozen tissues. The mutation results demonstrated > 94.0% concordance in all variants, with Kappa coefficient > 0.500 in 64.3% (83/129) of variants. At the gene level, concordance ranged from 73.8% to 100.0%, with Kappa coefficient > 0.500 in 81.3% (13/16) of genes. Conclusions: The results of mutation analysis performed with a multi-gene panel and FFPE and fresh frozen tissue were highly concordant in patients with CRC, at both the variant and gene levels. There were, however, some important differences in mutation results between the two tissue types. Therefore, fresh frozen tissue should not routinely be replaced with FFPE tissue for mutation analysis with a multi-gene panel. Rather, FFPE tissue is a reasonable alternative for fresh frozen tissue when the latter is unavailable.